Status of land conservation bias of agricultural technological progress in China：A measure based on agricultural input-biased technological progress - Han, Haibin; Zhao, Huixin (Journal of agricultural resources and environment, 2023)
为探究中国农业技术进步的偏向性特征，构建基于投入导向方向性距离函数的Malmquist-Luenberger生产率指数模型，在此基础上对 1997—2019年中国 30个省份农业投入偏向型技术进步进行测度，进而深入分析中国农业技术进步的土地节约偏向时空演变特征。结果表明：中国农业全要素生产率整体上呈现增长趋势，年均增长2.87%，技术进步是农业全要素生产率增长的重要因素。IBTC（投入偏向型技术进步）指数在各个年份均大于1，农业技术进步具有投入偏向性并且整体上偏向节约土地。具体来说，虽然在土地与劳动力之间偏向节约劳动力，但在土地与农业机械、土地与化肥、土地与农药等投入要素之间均偏向节约土地。从时序特征来看，农业技术进步的土地节约偏向随时间推移逐渐减弱；从空间分布来看，农业技术进步在东部地区的土地节约偏向程度强于中部和西部地区。研究表明，未来应在进一步优化农业生产要素结构的同时，从强化农业技术创新与应用、制定差异化技术进步发展路径、完善农业要素市场等方面出发，深入推进农业土地节约集约利用，实现农业可持续发展。To explore the bias characteristics of agricultural technological progress in China, the Malmquist–Luenberger productivity index based on the input-oriented directional distance function was used to measure agricultural input-biased technological progress in 30 Chinese provinces from 1997 to 2019, thus providing an in-depth analysis of the spatial and temporal evolutionary characteristics of the land-saving bias of agricultural technological progress in China. The study produced several interesting results：agricultural total factor productivity in China show